(untitled) (Journal of National Institute of Ophthalmology, 2023)
Purpose: To evaluate the clinical outcome of Amniotic Membrane Transplantation (AMT) in chemically injured eyes for ocular surface reconstruction. Methods: A prospective study of 30 consecutive chemically injured eyes was performed from December 2022 to May 2023 in National Institute of Ophthalmology & Hospital (NIO&H), Dhaka, Bangladesh. Twenty-seven patients (30 eyes having corrosive chemical injuries) were included in the study according to the inclusion & exclusion criteria. AMT was performed within 21 days of injury by single surgeon with modified surgical procedure. Post operative evaluation was done by Snellen chart, slit lamp biomicroscope and Schirmer-II test. Results: After 3 months of AMT, there was no pain or inflammation. Improvement of vision found in 20 (66.67%) of 30 eyes, 4 (13.33%) eyes of rest 10 eyes showed inaccurate Projection of Rays (PR) vision and rest 6 (20.0%) eyes of rest 10 eyes found deteriorated vision. Epithelialization occurred in all eyes. Twenty-four (80.0%) eyes had limbal stem cell deficiency and they experienced superficial corneal vascularization. Symblepharon was seen in 18 (60.0%) eyes, 6 (20.0%) of these 18 eyes developed marked conjunctival shortening with ankyloblepharon. None of the eyes showed perforation. Conclusions: AMT increases patient comfort and reduces inflammation. In mild burns, AMT alone restores corneal and conjunctival surfaces. In moderate to severe burns, it reduces conjunctival scarring sequelae, but does not prevent the sequelae of limbal stem cell deficiency that requires further limbal stem cell transplantation. In the acute stage, AMT has a protective role against the progressive melting and perforation. J.Natl.Inst.Ophthalmol.2023;6(1): 21-26